A Nanodrug Consisting Of Doxorubicin And Exosome Derived From Mesenchymal Stem Cells For Osteosarcoma Treatment In Vitro - Wei H; Chen J; Wang S; Fu F; Zhu X; Wu C; Liu Z; Zhong G; Lin J (International Journal of Nanomedicine, 2019)
Hongxiang Wei,1,* Jinyuan Chen,2,* Shenglin Wang,1,* Feihuan Fu,3 Xia Zhu,1 Chaoyang Wu,1 Zhoujie Liu,4 Guangxian Zhong,1 Jianhua Lin1 1Department of Orthopaedics, The First Affiliated Hospital of Fujian Medical University, Fuzhou 350004, People’s Republic of China; 2Department of Centralab, The First Affiliated Hospital of Fujian Medical University, Fuzhou 350004, People’s Republic of China; 3Department of Endocrinology, The County Hospital of Anxi, Anxi 362400, People’s Republic of China; 4Department of Pharmacy, The First Affiliated Hospital of Fujian Medical University, Fuzhou 350004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guangxian Zhong; Jianhua LinDepartment of Orthopaedics, The First Affiliated Hospital of Fujian Medical University, Fuzhou 350004, People’s Republic of ChinaTel/fax +86 591 87981029Email zhongguangxian@163.com; jianhual@126.comPurpose: The primary goal of the present study was to develop the nano-drug consisting of doxorubicin and exosome derived from mesenchymal stem cells, and to explore its effect on osteosarcoma in vitro.Methods: The exosomes were isolated from bone marrow MSCs (BM-MSCs) by an Exosome Isolation Kit. The exosome-loaded doxorubicin (Exo-Dox) was prepared by mixing exosome with Dox-HCl, desalinizing with triethylamine and then dialyzing against PBS overnight. The nanoparticle tracking analysis (NTA) and transmission electron microscope (TEM) were used to characterize of the exosome and Exo-Dox. The cytotoxicity of Exo-Dox was determined by CCK-8 assay. Further, the cellular uptake of different drugs was analyzed using inverted fluorescence microscope and flow cytometry.Results: The typical exosome structures can be observed by TEM. After loading with doxorubicin, its size is larger than free exosome. Compared with the free Dox, the prepared Exo-Dox showed enhanced cellular uptake efficiency and anti-tumor effect in osteosarcoma MG63 cell line but low cytotoxicity in myocardial H9C2 cell line.Conclusion: The prepared Exo-Dox could be used as an excellent chemotherapeutic drug for treatment of osteosarcoma in vitro. Considering the tumor-homing feature of BM-MSCs, the Exo-Dox may be a good candidate for targeted osteosarcoma treatment in future study.Keywords: exosome, mesenchymal stem cells, doxorubicin, osteosarcoma